1989
DOI: 10.1111/j.1365-2141.1989.tb07656.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fresh versus stored blood on post‐operative bleeding after coronary bypass surgery: a prospective randomized study

Abstract: In a prospective study, 237 patients undergoing a primary coronary bypass operation were randomized to receive 2 units of fresh whole blood (study group) or stored (2-5 d) blood (control group) at the end of the extracorporeal circulation. Serious post-operative bleeding necessitating a re-thoracotomy occurred in 4.2% of all patients with an equal distribution over the two groups. Post-operative haemoglobin content and platelet counts were higher in the study group, but the differences were small and clinicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 16 publications
0
35
2
Order By: Relevance
“…Although close to a dozen RCTs have been published on the relationship between storage duration and adverse outcomes [115][116][117][118][119][120][121][122][123][124], the majority have been either small or not adequately powered to evaluate mortality. Moreover, none of them have found any significant differences in outcomes between fresh and old subgroups of transfusion recipients across a variety of clinical settings.…”
Section: Randomised Controlled Trials (Rct)mentioning
confidence: 99%
See 1 more Smart Citation
“…Although close to a dozen RCTs have been published on the relationship between storage duration and adverse outcomes [115][116][117][118][119][120][121][122][123][124], the majority have been either small or not adequately powered to evaluate mortality. Moreover, none of them have found any significant differences in outcomes between fresh and old subgroups of transfusion recipients across a variety of clinical settings.…”
Section: Randomised Controlled Trials (Rct)mentioning
confidence: 99%
“…These have included healthy volunteers [67,[80][81][82], numerous retrospective and prospective observational studies [77,, and a handful of older [115][116][117][118][119][120][121][122][123], more recent [124], and ongoing randomised controlled trials. Overall, study results have been conflicting and affected by multiple methodological issues including confounding, systematic bias, limited external validity and multiple statistical shortcomings.…”
Section: Current State Of Clinical Evidence On the Clinical Relevancementioning
confidence: 99%
“…30 The few randomized trials have been limited by small size 31 or restrictive transfusion criteria. 32 Recently, the large multicenter ARIPI trial 33 demonstrated that neonates randomized to transfusion of red cell units < 7 days old compared to usual practice experienced no difference in the composite outcome of major neonatal morbidity. Several large multicenter randomized trials are currently enrolling adult patients, including RECESS 28 (cardiac surgery patients; NCT00991341), Canadian ABLE 34 (ICU patients; ISRCTN44878718) and TRANSFUSE (critically ill patients in Australia and New Zealand; NCT01638416).…”
Section: Discussionmentioning
confidence: 99%
“…30 The few randomized trials have been limited by small size 31 or restrictive transfusion criteria. 32 Recently, the large multicenter ARIPI trial 33 demonstrated that neonates randomized to transfusion of red cell units < 7 days old compared to usual practice experienced no difference in the composite outcome of major neonatal morbidity. Several large multicenter randomized trials are currently enrolling adult patients, including RECESS 28 (cardiac surgery patients; NCT00991341), Canadian ABLE 34 (ICU patients; ISRCTN44878718) and TRANSFUSE (critically ill patients in Australia and New Zealand; NCT01638416).…”
Section: Discussionmentioning
confidence: 99%